Optimization Of Concentration Of Clove (Syzygium Aromaticum) Extract On Reduction Of Histamine Content During Fermentation Of Idli Batter: Life Sciences-Food Science And Technnology - Praba K, Lakshmi; Mohan R, Jagan; M, Loganathan (International Journal of Life Science and Pharma Research, 2022)
Fermented foods are rich in nutritional profile and idli batter has its attention as it is a short term stored fermented food and now considered globally. The fermented batter may contain histamine which are produced during fermentation. The clove extract was known for its antimicrobial activity along with lots of medicinal value. Hence an attempt has been made to optimize the concentration of clove extract for addition in idli batter during fermentation to reduce the production of histamine. The effect of clove on the physiochemical parameters such as pH, color, titratable acidity was analyzed during storage period (0,2,4,6 hours) and it was found that the physiochemical parameters were not affected during the storage hours. The titratable acidity of the idli batter and clove added idli batter was found to be in the range of 0.16-0.18 and 0.10 - 0.28 % during the storage period. The Microbial load were also observed by analyzing the total plate count during storage hours and it reduced the microbial count from 9.05 CFU/g to 8.60 CFU/g during the storage period of 6 h in the clove extract added idli batter. Histamine producers were isolated using Nivens agar media. The histamine content in the clove extract added idli batter was found to be low at 6th hr (0.06 mg/kg.) The GC-MS analysis on phytocompounds in clove revealed that eugenol is a major compound present in clove which may be responsible for antibacterial activity and reduce the histamine producing organism. The histamine content in the control and clove extract idli batter was analyzed using modified colorimetric method and revealed that the addition of clove extract reduced the histamine content during storage period that can help in increased shelf life of idli batter.